2020
DOI: 10.1186/s13570-020-00161-6
|View full text |Cite
|
Sign up to set email alerts
|

A One Health framework for integrated service delivery in Turkana County, Kenya

Abstract: Pastoralists in sub-Saharan Africa have limited access to public services due to their mobile lifestyle, economic and political marginalization, and the limited health infrastructure that is common to arid and semi-arid lands (ASALs) where they primarily reside. This often results in poor health outcomes, including increased rates of maternal, neonatal, and under-5 mortality. One Health approaches that integrate human and animal health service delivery can help to improve pastoralists' health through increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 24 publications
(31 reference statements)
1
12
0
Order By: Relevance
“…Hence, mobile screening using the regional mobile health teams, one health approach and mobile DOTs through engaging community leaders can be useful strategies to enhance case finding and treatment adherence in pastoralist communities. The one health approach that integrates human-animal health services has been an effective and efficient mode of service delivery for pastoralists [ 58 ]. This study was conducted as part of one health approach in the setting and a related study has shown satisfactory results in community-based integrated disease surveillance, TB was not reported though.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, mobile screening using the regional mobile health teams, one health approach and mobile DOTs through engaging community leaders can be useful strategies to enhance case finding and treatment adherence in pastoralist communities. The one health approach that integrates human-animal health services has been an effective and efficient mode of service delivery for pastoralists [ 58 ]. This study was conducted as part of one health approach in the setting and a related study has shown satisfactory results in community-based integrated disease surveillance, TB was not reported though.…”
Section: Discussionmentioning
confidence: 99%
“…Recognition of the fact that EID outbreaks are likely to become more common may lend new importance to the study of resilience in health systems, especially among those of locally-situated communities. Additionally, a recognition of the human-animal interface as a locus of risk may lead to the integration of human and veterinary health systems, which would yield a variety of One Health benefits (Griffith et al, 2020). That said, I think that the limited case studies that follow show that there is real promise in discovering EIDs by using local knowledge.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…An ongoing wave of locusts in the GHA has led to the destruction of crops and pasture, with climate conditions expected to result in a dramatic increase in locust numbers during the coming months (Regional Desert Locust Alliance 2020). COVID-19 may limit entry into pastoral areas by Table 3 Examples of a One Health approach in pastoral areas in the GHA (Griffith et al 2020;Kamadjeu et al 2015;Lankester et al 2019;Mtui-Malamsha et al 2020;Musoke et al 2016;Ndejjo et al 2019;Onyango et al 2019 locust control personnel and result in personal protective equipment (PPE) "competition," as both locust control and health activities require PPE. Designation of locust control as essential can ensure access to pastoral areas, while a coordinated response by governments and development partners can help to ensure that PPE specialized for use in pesticide application is available (Regional Desert Locust Alliance 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Human health programmes often fail to reach pastoralists in the GHA due to their inherent mobility and marginalization, and the limited health infrastructure in the region’s arid and semi-arid lands (ASALs) (Dubale and Mariam 2007 ; Griffith et al 2020 ). Mobility is not only a defining and differential feature of pastoralist livelihoods, but it is also essential to the present and future viability of livestock production in most of the world’s drylands (de Jode 2010 ; Nugteren and Le Côme 2016 ; Manzano and Salguero 2018 ; Molina-Flores et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%